2009
DOI: 10.4314/jae.v12i2.47048
|View full text |Cite
|
Sign up to set email alerts
|

Policy Issues in the Structure, Conduct and Performance of Banana Market in Anambra State, Nigeria

Abstract: This study described the structure, conduct and performance of banana market in Anambra State of Nigeria. The specific objectives are to describe the structure of the banana market; analyze the conduct of the banana market; determine banana market performance; and examine the major problems of banana marketing in the area. One hundred and twenty respondents spread in six major urban centers in the State and their concomitant major markets were randomly selected for interview. Descriptive statistics, Gini coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…0 (zero) corresponds to perfect equality and 1 (one) corresponds to perfect inequality [35]. The Gini coefficient summarizes the Lorenz curve which compares the cumulative shares of the product ordered from small range to the large shares of the product that would accrue to the sellers and the producers under perfect equality (the diagonal) and the total area under the line of perfect equality [36]. In graphical terms, the Gini index is the ratio of the area between the Lorenz curve and the line of perfect equality.…”
Section: Gini Coefficient and Lorenz Curvementioning
confidence: 99%
“…0 (zero) corresponds to perfect equality and 1 (one) corresponds to perfect inequality [35]. The Gini coefficient summarizes the Lorenz curve which compares the cumulative shares of the product ordered from small range to the large shares of the product that would accrue to the sellers and the producers under perfect equality (the diagonal) and the total area under the line of perfect equality [36]. In graphical terms, the Gini index is the ratio of the area between the Lorenz curve and the line of perfect equality.…”
Section: Gini Coefficient and Lorenz Curvementioning
confidence: 99%
“…It further reveals that pineapple is highly demanded in the study area and that there is the need to encourage current pineapple farmers for increased production of the crop. The result appears convincing because the state is reported to have large population and the biggest market in West Africa (Enibe et al, 2008). The result also supports Iwuchukwu, Udoye and Onwubuya (2013) whose study saw the need to encourage pineapple farmers for increased output of the crop.…”
Section: Sources Of the Pineapple Marketed In Anambra Statementioning
confidence: 62%
“…The primary data were purposively collected from city markets of Onitsha and Awka. Onitsha was purposively chosen because it contains the biggest market in West Africa (Enibe et al, 2008) while Awka was purposively selected because it is the capital city of the study area. Main market, Ose, Ochanja and bridge-head market areas were selected from Onitsha commercial city while Eke, Nkwo Amaenyi, Aroma junction and UNIZIK temporary site market areas were chosen from Awka Capital city.…”
Section: Methodsmentioning
confidence: 99%
“…Tiku et al (2012) found a Gini coefficient of 0.65 and 0.54 for merchants and processors respectively, indicating an oligopoly market structure among palm oil marketers in Cross River State, Nigeria. However, different and contrasting results were reported by Enibe, et al, (2008) in the case of banana marketing in Anambra State, Nigeria where the Gini coefficients were 0.21 and 0.17 for wholesalers and retailers respectively, depicting a competitive market. Haruna, et al, (2012) made a similar observation in their study on the Market structure, conduct, channels and margins of dry season Okra vegetable in South-Eastern Nigeria.…”
Section: Gini Coefficientmentioning
confidence: 75%